Massive elliptical galaxies : From cores to haloes - Lintott, C; Ferreras, I; Lahav, O (2005)
In the context of recent observational results that show massive ellipticals were in place at high redshifts, we reassess the status of monolithic collapse in a LCDM universe. Using a sample of over 2000 galaxies from the Sloan Digital Sky Survey, by comparing the dynamical mass and stellar mass (estimated from colours) we find that ellipticals have `cores' which are baryon-dominated within their half-light radius. These galaxies correspond to 3-sigma peaks in the spherical collapse model if the total mass in the halo is assumed to be 20 times the dynamical mass within the half-light radius. This value yields stellar mass to total mass ratios of 8%, compared to a cosmological baryon fraction of 18% derived from WMAP3 alone. We further develop a method for reconstructing the concentration halo parameter c of the progenitors of these galaxies by utilizing adiabatic contraction. Although the analysis is done within the framework of monolithic collapse, the resulting distribution of c is log-normal with a peak value of c~3-10 and a distribution width similar to the results of N-body simulations. We also derive scaling relations between stellar and dynamical mass and the velocity dispersion, and find that these are sufficient to recover the tilt of the fundamental plane.